The Impact of Sustainability and Cyber Security Policies on Firm Performance: Evidence from ASEAN Listed Companies - Mohd Ariffin, Mohd Shazwan; Abdul Malak, Siti Seri Delima; Wan-Hussin, Wan Nordin; Ripain, Noraizan (International Journal of Economics, Management and Accounting, 2025)
This paper explores firm performance evaluation, expanding beyond traditional return on assets to include Tobin’s Q. Sustainability and cybersecurity policies are identified as crucial factors influencing corporate success. The study analyzes 206 publicly listed companies in Malaysia, Thailand, and Singapore within the ASEAN region, using data from Refinitiv Eikon and multiple regression techniques. The results reveal a significant impact of sustainability and cybersecurity policies on firm performance as measured by Tobin’s Q. The findings support the theoretical frameworks of agency cost and stakeholder theories. Future research should consider broadening the study’s scope to include additional datasets from other ASEAN-listed companies to enhance the understanding of the relationship between policies and firm performance.